2014
DOI: 10.4236/ijcm.2014.515124
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synergistic Protective Efficacy of Atovaquone and Diclazuril on Fetal-Maternal Toxoplasmosis

Abstract: Over 1 billion people globally are estimated to be infected with Toxoplasma gondii with severe or unknown consequences and no safe and effective therapies are available against congenital or persistent chronic infection. We propose that atovaquone and diclazuril synergistically protect against fetal-maternal toxoplasmosis. Methods Programmed pregnant mice were treated with atovaquone and diclazuril monotherapy, or combined (atovaquone + diclazuril) therapy and infected with tachyzoites (0, 300, 600) and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
0
12
0
6
Order By: Relevance
“…Murphy et al showed that erythrocyte G proteins are functional and that propranolol, as an antagonist of G protein-coupled b-adrenergic receptors, inhibits G protein activity in erythrocytes. They also discovered that like other b 2 antagonists, propranolol inhibited blood-stage parasite growth, such that propranolol used in combination with existing antimalarial agents in cell culture reduced the 50% and 90% inhibitory concentrations for existing drugs against P. falciparum and was also effective in reducing drug doses in animal models of infection (33).…”
Section: Figmentioning
confidence: 99%
See 4 more Smart Citations
“…Murphy et al showed that erythrocyte G proteins are functional and that propranolol, as an antagonist of G protein-coupled b-adrenergic receptors, inhibits G protein activity in erythrocytes. They also discovered that like other b 2 antagonists, propranolol inhibited blood-stage parasite growth, such that propranolol used in combination with existing antimalarial agents in cell culture reduced the 50% and 90% inhibitory concentrations for existing drugs against P. falciparum and was also effective in reducing drug doses in animal models of infection (33).…”
Section: Figmentioning
confidence: 99%
“…Spiramycin monotherapy can be effective during the early stage of pregnancy to prevent prenatal transmission. More than 50% of patients treated with spiramycin retained T. gondii DNA in blood and remained infected (2). So, for prevention/eradication of the chronic infection or protection against congenital toxoplasmosis, current chemotherapy is not safe or effective.…”
mentioning
confidence: 99%
See 3 more Smart Citations